Evaluation of brassiere for fit and comfort - Manipon, Cristina Moonyeen C.; Florendo, Racquel B. (2001.)
This study focuses on the evaluation of the fit and comfort of brassiere according to the issues/problems and level of satisfaction experienced by selected female college students. It attempts to prove that brassieres that are correctly made are comfortable and will fit the body well. The descriptive method was used for gathering and analyzing data. Survey questionnaires were distributed to 30 residents of the Sampaguita Residence Hall. Incidental sampling was used to select samples. This design is applied to those samples that are taken because they are the most available. The recommended statistical treatments for are evaluative study are weighted arithmetic mean, frequency distribution, and percentages. In this study it was determined that a majority of the respondent have a cup A bra size. The study also revealed that there are problems regarding fit and comfort of the bra but they are very minimal because they can adequately judge a good quality bra. The respondents are moderately satisfied with the fit and comfort of brassiere available in the market. Consumers have a concept of what constitutes a well-fitted and comfortable bra. They have different needs and reasons for the style of bra they choose but the most important for them is that the parts of the bra fits the contours of their body. Therefore, the construction of bra is important because a bra that is correctly made according to its function is comfortable to wear and will fit the body well.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Brassieres